Keterbukaan Diri Dalam Ta'aruf Dan Keputusan Menikah ( Studi Korelasi AntaraKeterbukaan DiriDalam Ta'aruf Dengan Keputusan Menikah Kelompok Tarbiyah PKS Cabang Polokarto) - Aryanto, Aji Anung (2016)
All individual will face marriage decision. One of many way in introducing process to a marriage is Ta'aruf. Self-disclosure happen in process of giving information to a potential partner in purpose of marriage. Meeting process is purposed to build foundation of marriage. Self-disclosure happen in Ta'aruf process that done by PKS Party member in marriage decision. Marriage decision making depend on Ta'aruf process. Purpose of this research is to know relation between self-disclosure in Ta'aruf process with marriage decision in PKS Tarbiyah group, brace Polokarto. This research using Quantitative method. In collecting data, researcher spread questionnaire to 80 respondent that was member of PKS Tarbiyah, branch Polokarto that already facing Ta'aruf process. Analysis data in this research using correlation study. The result show that r count > r table (0,589 > 0.219) and signification 0,000 smaller than 0,05. According to data processing, can be concluded that there are correlation between self-disclosure in Ta'aruf process with marriage decision. Correlation coefficient 0,589 show strong relation and having same direction. Its mean that more self-disclosure in Ta'aruf, marriage decision will be stronger